Coinfection of EBV with other pathogens: a narrative review - Ebrahimi, Fatemeh; Rasizadeh, Reyhaneh; Sharaflou, Shabnam; Aghbash, Parisa Shiri; Shamekh, Ali; Jafari-Sales, Abolfazl; Bannazadeh Baghi, Hossein (Frontiers in Virology, 2024)
The Epstein-Barr viwrus (EBV) is a common herpesvirus that affects more than 90% of people worldwide. Even while EBV infections are frequently asymptomatic, they can cause autoimmune diseases and a number of cancers, especially in those with impaired immune systems. The intricate relationships between EBV and other coinfecting pathogens, including as human immunodeficiency virus (HIV), human papilloma virus (HPV), cytomegalovirus (CMV), and Plasmodium species, are examined in this study. We investigated the fundamental processes of these coinfections, their effects on the course of the disease, and their practical ramifications. The study reviewed how co-infections with EBV might modify immune responses, promote oncogenesis, and make treatment plans more challenging. In this review, we also discussed current therapeutic strategies, such as targeted molecular interventions, EBV vaccines, and adoptive T-cell therapy. The review underscores the need for more research to provide more focused and effective therapies that address the mutually reinforcing effects of numerous infections in disorders linked with EBV.